FACTORS AFFECTING THE TIMELESS OF SUBMITTING FINANCIAL STATEMENTS (EMPIRICAL STUDY OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2021) - Helmina, Monica Rahardian Ary; Wulandari, Niki (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The aim of the research was to find aout what factors can influence the timeliness of submitting a company’s financial report. The research population and sample were 156 manufacturing companies listed on the IDX for the 2019-2021 period. The variables taken to assess timeliness are profitability, leverage, company size, audit quality, managerial ownership, institutional ownership, and audit opinion. Secondary data in the form of company financial eports were collected and then analyzed using the logistic regression method. Based on the research results,evidence was obtained that the variables that influence the timeliness of submitting financial reports are profitability, company size, audit quality, managerial ownership, institutnal ownership, and audit opinion. The variable of leverage have no effect on the timeliness submission on financial statement.